Development of Exercise Smash, Lob and Backhand Models in Bulutangkis Based on Training Variation for Beginner - Rahmat, Ade Rahmat; Asmawi, Moch Asmawi; Tangkudung, James Tangkudung; Dlis, Firmansyah Dlis; Saputra, Surya Adi (Journal of Education, Health and Sport, 2019)
The purpose of this research and development is to produce a model practice badminton smash and lob-based variation of tools for novice players and determine the effectiveness, efficiency and appeal of players to the model created. This study uses research methods development Research & Development (R & D) from Borg and Gall. The subjects in this research and development is a club of players consisting of 40 players.The instruments are used in research and development are the instrument test the suitability and the results of the motion that is used to collect motion data smash and lob, while the stages in the research and development are, in stages: (1) analysis of needs, (2) the expert evaluation (evaluation the initial product); (3) the trial is limited (small group trial); and (4) the main test (field testing). Based on the results of the development can be concluded that: (1) With the development of this type of training smash and lob badminton-based variation of tools for novice players can be developed and applied in the training process badminton (2) The model of this type of training smash and lob badminton-based variation of tools for players beginners who have developed, acquired evidence of this improvement is the show on the test results data from the pretest and post-test any significant difference between before and after treatment models.